Paul Celan Today - Böttiger, Helmut,Caradonna, Chiara,Colin, Amy-Diana,Connolly, Thomas C.,Corbea-Hoisie, Andrei,Draesner, Ulrike,Elston, Cherilyn,Eskin, Michael,Grünbein, Durs,Ivanovic, Christine,Kiefer, Anselm,Kligerman, Eric,Leeder, Karen,Louth, Charlie,McMurty, Áine,Mendicino, Kristina,Miglio, Camilla,Pajević, Marko,Thouard, Denis,Vice, Sue,Waal, Edmund de,Waterhouse, Peter (De Gruyter, 2021)
Marking Paul Celan's 100th birthday and the 50th anniversary of his death, this volume endeavours to answer the following question: why does Celan still matter today – more than ever perhaps? And why should he continue to matter tomorrow? In other words, the volume explores and assesses the enduring significance of Celan's life and œuvre in and for the 21st century. Boasting cutting-edge research by international scholars together with original contributions by contemporary artists and writers, this book attests to, on the one hand, the extent to which large swathes of contemporary philosophy, poetics, literary scholarship, and aesthetics have been indebted to Celan's legacy and are simply unthinkable without it, and, on the other hand, to the malleability, adaptability, breadth and depth of Celan's poetics, which, like the music of The Beatles, Led Zeppelin, or Queen, is reborn and rediscovered with every new generation.
10.1515/9783110658330
Keywords: Aufsatzsammlung; Celan; Paul; Literature and Philosophy; Literature and Politics; Literature and the Arts; Paul Celan; Poetry; Rezeption; LITERARY CRITICISM / General